Meningkatkan Hasil Belajar Matematika Materi Perkalian dengan Menggunakan Media Pembelajaran Konkret - Mengkido, Meyland Rikhar; Gagaramusu, Yusdin Bin M; Khairunnisa, Khairunnisa; Zulnuraini, Zulnuraini; Guci, Ammar Abdullah Joni (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to improve the learning outcomes of mathematics multiplication material for second-grade students at SD GKST Talabosa using concrete learning media. The study involved 12 students, consisting of 9 male students and 3 female students, and employed a classroom action research method with Problem-Based Learning (PBL) approach. The concrete media used were stick pieces and straws. In the first cycle, the results showed 75% classical completeness and an average score of 88.33%, with 9 students achieving the competency standard and 3 students not yet achieving it, with the lowest score being 65 and the highest score being 97.5. Based on these findings, adjustments and improvements were made for the second cycle. In the second cycle, all students achieved the minimum completeness criteria, with the lowest score being 97.5 and the highest score being 100, and an average score of 99.79%. Based on the research conducted in cycles I and II, it shows that the use of concrete media in mathematics learning for second-grade students at SD GKST Talabosa can improve student learning outcomes.   Keywords: Learning Outcomes, learning media, Concrete Learning Media, Mathematics Learning, Multiplication